Human-Ai Friendship : A Study of Interactions and Relationship Development between Users and Social Chatbots - Sharma, Khyati (My University, 2025)
This research explores the emerging phenomenon of human–AI friendship by examining how users form emotional and interpersonal bonds with social chatbots, specifically Replika and Kuki. The study was conducted in two parts to investigate both longitudinal and situational dynamics of human–AI interaction. Study 1 employed a four-week interaction either with Replika or Kuki. Open coding was employed in the first study to identify the major themes emerging from interactions between users and social chatbots.Quantitative measures were administered to assess perceived agency and emotional Intimacy. Results indicated that Replika was better as compared to Kuki to foster higher engagement because it supported memory retention and personalized interactions that facilitated higher perceived intimacy and emotional attachment. Based on these findings, Study 2 focused exclusively on Replika, and three structured scenarios were designed to explore the themes identified in Study 1 more deeply (emotional support, understanding, and shared activities). Self report measures were used to measure anthropomorphism, empathy, and social presence, along with a thematic analysis of chat transcripts. The findings revealed that relational cues embedded in chatbot responses significantly influenced users’ perceptions of trust, warmth, and companionship. The key finding of the study was that Replika can mimic human–human friendship more effectively . This is largely due to Replika’s ability to display unconditional positive regard as a supportive companion, understand through cognitive empathy, form emotional connections through shared activities, and engage users with its broad knowledge of topics like movies and music, which helps it resonate more deeply with users’ interests and emotions.This research contributes to the evolving understanding of social chatbots as social actor and highlights the psychological mechanisms through which individuals experience companionship, despite the absence of true reciprocal consciousness in AI. The implications of this study extend to therapeutic, educational, and companionship applications of social chatbots .
Keywords: Human-AI Friendship; Social Chatbots; Replika; Kuki; Thematic Analysis; Human–Computer Interaction